Cryopreserved-thawed human embryo transfer: spontaneous natural cycle is superior to human chorionic gonadotropin-induced natural cycle - Fatemi, Human Mousavi; Kyrou, Dimitra; Bourgain, Claire; Van den Abbeel, Etienne; Griesinger, Georg; Devroey, Paul (Fertility and sterility, 2010)
To assess whether there is a difference in the ongoing pregnancy rate after transferring frozen-thawed embryos in natural cycles with spontaneous LH-P rise compared with natural cycles controlled by hCG for final oocyte maturation and ovulation. Randomized controlled trial. Tertiary referral center. A total of 168 patients were assigned randomly to undergo frozen ET on day 3 from October 2007 until November 2008. Finally, analysis was performed in 124 patients; 61 belonged to the spontaneous LH group and 63 to the hCG group. In the spontaneous LH group the transfer was planned 5 days after the LH surge. In the hCG group, the cryopreserve ET was planned 5 days after the administration of 5000 IU of hCG, when an endometrial thickness of ≥7 mm and a follicle of ≥17 mm were present on ultrasound examination. Ongoing pregnancy rate. The study was terminated early, when a prespecified interim analysis found a significantly higher ongoing pregnancy rate in the spontaneous LH group as compared with the hCG group (31.1% vs. 14.3%; difference 16.9%, 95% confidence interval 4.4%-28.8%). The results suggest the superiority of the natural cycle as compared with the natural cycle controlled by hCG administration in cryothawed ET cycles.